2022
DOI: 10.1073/pnas.2204574119
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-dependent phosphorylation of NRAMP1 by CPK21 and CPK23 facilitates manganese uptake and homeostasis inArabidopsis

Abstract: Homeostasis of the essential micronutrient manganese (Mn) is crucially determined through availability and uptake efficiency in all organisms. Mn deficiency of plants especially occurs in alkaline and calcareous soils, seriously restricting crop yield. However, the mechanisms underlying the sensing and signaling of Mn availability and conferring regulation of Mn uptake await elucidation. Here, we uncover that Mn depletion triggers spatiotemporally defined long-lasting Ca 2+ oscillations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 67 publications
(92 reference statements)
1
31
0
Order By: Relevance
“…Histochemical analysis of GUS activity of 7‐d‐old ProNRAMP6:GUS , ProCPK21:GUS , and ProCPK23:GUS transgenic plants showed that they have similar tissue‐specific expression patterns and all exhibited staining in root tips (Fig. S1), which was consistent with recently published research (Fu et al ., 2022). The results suggested that a physiological interaction between NRAMP6 and CPK21/23 is possible in Arabidopsis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Histochemical analysis of GUS activity of 7‐d‐old ProNRAMP6:GUS , ProCPK21:GUS , and ProCPK23:GUS transgenic plants showed that they have similar tissue‐specific expression patterns and all exhibited staining in root tips (Fig. S1), which was consistent with recently published research (Fu et al ., 2022). The results suggested that a physiological interaction between NRAMP6 and CPK21/23 is possible in Arabidopsis .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, nramp1/6 double mutants enhanced the sensitive phenotype of nramp1 single mutant in response to Mn deficiency, which suggested that NRAMP6 and NRAMP1 cooperatively function under Mn deficient conditions, with NRAMP1 being the major player (Li et al ., 2019). Our recently published article has showed that CPK21/23 phosphorylate and activate Mn transporter NRAMP1 to enhance plant tolerance to Mn deficiency (Fu et al ., 2022). Although CPK21/23 act upstream of both NRAMP1 and NRAMP6, the results from heterologous yeast complementing assays and Mn concentration analysis of transgenic plants suggested that the roles of CPK21/23 on NRAMP1 and NRAMP6 are, to some extent, specific to Mn‐deficiency and Cd stress responses (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whether Ca 2+ signaling plays an important role in plant response and tolerance to Mn deficiency remains unclear. This brief article highlights the recent results of Fu et al (2022), who revealed a Ca 2+ -CPK21/23-NRAMP1 axis as an important mechanism for plant tolerance and adaptation to low Mn.…”
mentioning
confidence: 76%